2008
DOI: 10.1212/01.wnl.0000303969.63165.34
|View full text |Cite
|
Sign up to set email alerts
|

Carotid plaque, a subclinical precursor of vascular events

Abstract: Background-Carotid atherosclerosis is a known biomarker associated with future vascular disease. The risk associated with small, nonstenotic carotid plaques is less clear. The objective of this study was to examine the association between maximum carotid plaque thickness and risk of vascular events in an urban multiethnic cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
236
2
17

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(262 citation statements)
references
References 38 publications
7
236
2
17
Order By: Relevance
“…Previous studies demonstrated that presence of carotid plaque was a more powerful predictor of cardiovascular events than intima-media thickness. [21][22][23][24] Carotid plaque score is useful as a means of semiquantitative analysis of degree of atherosclerosis. CPS is obtained by a wider range observation of the carotid arteries than intima-media thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that presence of carotid plaque was a more powerful predictor of cardiovascular events than intima-media thickness. [21][22][23][24] Carotid plaque score is useful as a means of semiquantitative analysis of degree of atherosclerosis. CPS is obtained by a wider range observation of the carotid arteries than intima-media thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin, the most abundant adipokine produced by adipocytes, provides an important association between obesity, insulin resistance, and related inflammatory disorders. Rundek et al found that adiponectin provides a small but significant contribution to variances in the carotid IMT 80) . Traditional cardiovascular risk factors explain only a small part of the variance observed in the carotid IMT.…”
Section: Associations Between the Carotid Imt And Biological Markersmentioning
confidence: 99%
“…The presence of carotid plaque and the carotid intima-media thickness (C-IMT) are known markers of subclinical or early atherosclerosis and are associated with an increased risk of cardiovascular disease in large epidemiological studies [1][2][3] . Associations between the progression of carotid plaque or C-IMT over time and cardiovascular events have also been reported 4,5) .…”
Section: Introductionmentioning
confidence: 99%